2012
DOI: 10.2165/11636320-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Triple Antihypertensive Therapy with the Olmesartan/Amlodipine/Hydrochlorothiazide Combination

Abstract: Registered at ClinicalTrials.gov identifier as NCT00923091.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 34 publications
2
36
0
5
Order By: Relevance
“…16 The study consisted of a double-blind safety run-in (weeks 0-2: period I), double-blind (weeks 3-10: period II), single-blind (weeks [10][11][12][13][14][15][16][17][18], and open-label treatment periods (weeks 18-54). The single-blind and open-label treatment periods are beyond the focus of the current report and are not described here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 The study consisted of a double-blind safety run-in (weeks 0-2: period I), double-blind (weeks 3-10: period II), single-blind (weeks [10][11][12][13][14][15][16][17][18], and open-label treatment periods (weeks 18-54). The single-blind and open-label treatment periods are beyond the focus of the current report and are not described here.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a factorial study in patients with moderate to severe hypertension investigated the addition of HCTZ 12.5 mg and 25 mg to OLM/AML treatment and found it provided statistically significant improvements in BP reduction and achievement of BP thresholds (ClinicalTrials.gov identifier: NCT00923091). 16 This multinational, phase III, randomized, double-blind study provides an opportunity to assess the efficacy of triple-combination therapy in higher-risk subgroups of hypertensive patients, including those with severe hypertension and other risk factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Information obtained from these analyses are of potential clinical relevance, since they can be effectively implemented by recommendations derived from international guidelines, in order to improve the clinical management and achieve the recommended blood pressure targets. In particular, recent studies have demonstrated that the implementation of rational and effective therapeutic regimes, mostly based on combination therapies, may promote higher rates of blood pressure control also in the setting of real practice [5][6][7].In this issue of High Blood Pressure and Cardiovascular Prevention, Kiselev and co-authors reported a detailed and comprehensive analysis of clinical factors that may have potential impact on the achievement of the blood pressure goals in a large sample of adult individuals with hypertension in the Ivanovo, Russia [8]. This study is part of the larger Russian Registry of Hypertension, Coronary Artery Disease and Chronic Heart Failure, which is a retrospective, continuous, nation-wide, web-based registry.…”
mentioning
confidence: 99%
“…Information obtained from these analyses are of potential clinical relevance, since they can be effectively implemented by recommendations derived from international guidelines, in order to improve the clinical management and achieve the recommended blood pressure targets. In particular, recent studies have demonstrated that the implementation of rational and effective therapeutic regimes, mostly based on combination therapies, may promote higher rates of blood pressure control also in the setting of real practice [5][6][7].…”
mentioning
confidence: 99%